Viscoelastic dynamics of a soft strip subject to a large deformation - Delory, Alexandre; Kiefer, Daniel A; Lanoy, Maxime; Eddi, Antonin; Prada, Claire; Lemoult, Fabrice (Soft matter, 2024)
To produce sounds, we adjust the tension of our vocal folds to shape their properties and control the pitch. This efficient mechanism offers inspiration for designing reconfigurable materials and adaptable soft robots. However, understanding how flexible structures respond to a significant static strain is not straightforward. This complexity also limits the precision of medical imaging when applied to tensioned organs like muscles, tendons, ligaments and blood vessels among others. In this article, we experimentally and theoretically explore the dynamics of a soft strip subject to a substantial static extension, up to 180%. Our observations reveal a few intriguing effects, such as the resilience of certain vibrational modes to a static deformation. These observations are supported by a model based on the incremental displacement theory. This has promising practical implications for characterizing soft materials but also for scenarios where external actions can be used to tune properties. We follow the propagation of guided elastic waves in a soft strip and study the effect of frequency and prestress on their velocities. The two fundamental in-plane modes are displayed: compression and flexion.